Occurrence of Self-medication in the Brazilian population as a preventive strategy for SARS-CoV-2 (Research, Society and Development, 2021)
The objective was to identify the existence of self-medication by people with the purpose of preventing SARS-CoV-2 and to analyze the potential worsening of this use to the human organism. It is a descriptive and analytical research, of a quantitative nature, where the data collection of this study was carried out through a semi-structured form, made available electronically, using the Google Forms tool. Inclusion criteria include: social network user and who answered the form in the period established by the researchers. There is a prevalence of female participants and people with primary and higher education, in which there was no predominance of self-medication. The highest rates of self-medication to the drugs Ivermectin and Azithromycin, most individuals purchased these drugs through the commercial pharmacy. Therefore, it is important to emphasize that drugs should not be ingested without medical guidance, which demonstrates the importance of health professionals as well as media vehicles, making the population aware of the care that should be taken and the risks that they may suffer when self-medicating.